Endoscopic ultrasound‐guided fine needle aspiration of accessory spleen: Cytomorphologic features and diagnostic considerations. Issue 7 (21st April 2020) - Gilani, Syed M.; Muniraj, Thiruvengadam; Farrell, James J.; Aslanian, Harry R.; Cai, Guoping
Abstract: Background: Accessory spleen/or splenule (AS) can involve pancreas/or peripancreatic tissue and present as a mass‐forming lesion, and on imaging studies, it stimulates concern for a neoplastic process. The current study reported the largest cohort of AS cases evaluated by endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA). Methods: We retrospectively reviewed our data base system for cases underwent EUS‐FNA for pancreatic/or peripancreatic lesions, with "AS" in diagnosis or in note/or with a clinical concern in the history, from January 2010 to August 2019. Corresponding cytology slides were re‐reviewed to identify the key cytomorphologic features. Results: We identified 25 AS cases from 15 female and 10 male patients with a mean age of 55 years. Most patients presented with non‐specific clinical symptoms or were identified as an incidental mass lesion. Majority of the lesions were located in or around the pancreatic tail region (68%) while the remainder in perisplenic region (32%). Rapid on‐site evaluation (ROSE) was performed in nearly half of the cases (48%). Cytologically, AS shows a mixed population of medium to small‐sized lymphocytes, clusters of lymphoid cells (LC), prominent vascularity (PV), scattered mixed inflammatory cells including eosinophils, and large platelet aggregates (LPAs). Among them, LC ( P = .0079), PV and LPAs were the most helpful features for cytological diagnosis. Conclusion: AS is a benign entity and may pose a diagnostic challenge due to its resemblance to a neoplastic process on imaging studies. EUS‐FNA is an important tool to recognize AS by identifying its key cytologic features, thus may help to avoid unnecessary surgical management.